2013
DOI: 10.1177/082585971302900301
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Care Personnel and Services: A National Survey in Thailand 2012

Abstract: Research on palliative care services in Thailand is incomplete. We conducted a countrywide cross-sectional postal survey to update the situation. We approached hospitals and asked them to respond to a questionnaire. The overall response rate of government hospitals was 61 percent (537 of 882 hospitals). Of these, 59 percent reported that they had personnel trained in palliative care; the majority had received less than a week of such training. In all, 60 percent of the hospitals reported that they offered pall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 16 publications
(22 reference statements)
0
11
0
2
Order By: Relevance
“…Recent published article regarding the education status of palliative care and palliative care service availability showed that majority of medical personnel take palliative care less than one week of short duration of training. [16] This factor may cause underused of opioids by physicians. Reasons for this include excessive concern about opioid-induced respiratory depression, tolerance, and addiction, as well as the impact of controlled substances regulations.…”
Section: Discussionmentioning
confidence: 99%
“…Recent published article regarding the education status of palliative care and palliative care service availability showed that majority of medical personnel take palliative care less than one week of short duration of training. [16] This factor may cause underused of opioids by physicians. Reasons for this include excessive concern about opioid-induced respiratory depression, tolerance, and addiction, as well as the impact of controlled substances regulations.…”
Section: Discussionmentioning
confidence: 99%
“…(2016), em seu estudo para avaliar as práticas de enfermagem para a avaliação da ansiedade no paciente com câncer, identificaram que estratégias multifacetadas, liderança e educação de enfermeiras na avaliação e análise da ansiedade são necessárias para melhorar o gerenciamento de sintomas em pacientes com câncer avançado. Phungrassami et al (2013) descreveram um modelo de cuidados paliativos hospitalares, no qual foi utilizado um banco de dados de hospitais registrado com as políticas e estratégias do Ministério da Saúde Pública da Tailândia. Neste estudo, foram incluídos profissionais enfermeiros, médicos e outros da saúde com tempo de trabalho em cuidados paliativos.…”
Section: Resultsunclassified
“…This may be explained by the fact that there is still a lack of health-care resources for terminally ill patients in Thailand, for example, the availability of hospices, long-term care beds, and palliative care personnel. 15 Without a palliative home care program, there would be very little support for the families to care the patients during their last days, and most patients have no other choice but to die in a hospital. Two other significant factors were found to increase the chance of home death.…”
Section: Discussionmentioning
confidence: 99%
“…14 A national survey by Phungrassami et al between January and April 2012 revealed that only 60% of hospitals in Thailand offered some kinds of palliative care service and 25% of these provided service without the assistance of any trained personnel, especially at the primary care level. 15 Moreover, the national health survey between October 2005 and September 2006 revealed that 53% of Thais died at home and 37% died in public hospitals. Approximately two-thirds of patients without health-care insurance as well as of UC beneficiaries died at home, whereas half of the patients who were CSMBS beneficiaries died in public hospitals.…”
Section: Introductionmentioning
confidence: 99%